Neutrophil and M2-polarized Macrophage Infiltration, Expression of IL-8 and Apoptosis in Mycoplasma hyopneumoniae Pneumonia in Swine. (November 2021) - Nueangphuet, Phawut; Suwanruengsri, Mathurot; Fuke, Naoyuki; Uemura, Ryoko; Hirai, Takuya; Yamaguchi, Ryoji
Summary: Mycoplasma hyopneumoniae ( Mhp ) is the primary pathogen of porcine enzootic pneumonia (PEP). Consolidated lung tissue from the cranioventral lung lobes of 15 pigs with PEP was collected for quantitative polymerase chain reaction, histopathology and immunohistochemistry. Histopathology revealed the co-existence of bronchial-associated lymphoid tissue hyperplasia with intra-alveolar neutrophils and macrophage infiltration in lesions of suppurative bronchopneumonia. Immunolabelling of infiltrated macrophages with CD163/CD204 indicated the presence of M2-polarized macrophages. Mhp antigen was detected on respiratory epithelial cells and in phagocytosed neutrophils. The intensity of Mhp immunolabelling and number of CD163/CD204-positive macrophages were correlated with the Mhp load in lung tissue ( r  = 0.87, 0.56, P  <0.05). IL-8 immunolabelling was mainly found in neutrophils and correlated with Mhp load, Mhp immunolabelling and histological lesion score ( r  = 0.70, 0.66, 0.64, P  <0.05), respectively. Apoptosis was seen in intra-alveolar cells and was correlated with Mhp load ( r  = 0.62, P  <0.05). It is postulated that IL-8 attracts neutrophils to the lesions, while M2-polarized macrophages are a major source of IL-10 and promote a Th2-type immune response.